2010
DOI: 10.1111/j.1440-1827.2010.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly genetic analysis of von Hippel-Lindau associated central nervous system hemangioblastoma

Abstract: Von Hippel-Lindau (VHL) disease is an autosomal dominant inherited cancer predisposition syndrome, characterized by development of a variety of neoplasms in multiple organs. Central nervous system hemangioblastoma (CHB) is the most common manifestation of VHL disease. The germline mutations in the VHL tumor suppressor gene are responsible for the inherited cancer predisposition syndrome. To expand the VHL mutation data and to investigate the tumorigenesis of VHL-associated CNS hemangioblastoma, 24 CHB tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
2
13
1
Order By: Relevance
“…These mutations occurred in four or more VHL families, and the occurrence rate of common mutations is estimated to be nearly 10% in the Western population (20,21). Although we did not identify any common mutations in our study, these mutations have been reported by others studying Chinese patients (6,8,9). China is geographically vast, and as such it is expected to present different mutation spectrums in different areas.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…These mutations occurred in four or more VHL families, and the occurrence rate of common mutations is estimated to be nearly 10% in the Western population (20,21). Although we did not identify any common mutations in our study, these mutations have been reported by others studying Chinese patients (6,8,9). China is geographically vast, and as such it is expected to present different mutation spectrums in different areas.…”
Section: Discussioncontrasting
confidence: 51%
“…Another manuscript by Zhang et al (6) described 26 germline mutations identified in 27 probands. Mao et al (7) reported VHL genetic findings in three other Chinese families, while Zhou et al (8) reported their findings of six distinctive germline mutations from ten Chinese families with VHL-associated CNS hemangioblastoma. Finally, Siu et al (9) found nine different mutations in nine other Chinese VHL families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,20,[22][23][24][25] There were totally 70 families that were clinically diagnosed as VHL disease and had the data of VHL mutations ( Table 3). The spectrum of VHL mutations in Chinese patients is comparable to the findings of large scale investigations from other countries, 11,21 but with some unique characteristics ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that degradome products of this matricellular protein may modulate the pathological angiogenesis in the retina [20]. The PLAGL1 (pleiomorphic adenoma gene-like 1) gene encodes a C2H2 zinc finger protein, which is a transcriptional regulator with anti-proliferative properties [21,22].…”
Section: Experimental Researchmentioning
confidence: 99%